Current Issues and Challenges in Polypropylene Foaming: A Review. Issue 6 (November 2015) - Mohebbi, Abolfazl; Mighri, Frej; Ajji, Abdellah; Rodrigue, Denis
Thermoplastic foams have several advantages in comparison with unfoamed polymers such as lightweight, high strength to weight ratio, excellent insulation property, high thermal stability, high impact strength and toughness, as well as high fatigue life. These outstanding properties lead cellular plastics to various industrial applications in packaging, automotive parts, absorbents, and sporting equipment. Nowadays, polypropylene (PP), because of its outstanding characteristics such as low material cost, high service temperature, high melting point, high tensile modulus, low density, and excellent chemical resistance, is a major resin in the foaming industry. However, foaming of conventional PP is limited by its low melt strength leading to poor cell morphology, cell rupture/coalescence and limited density reduction. To improve PP melt strength, several strategies including particle addition as nucleating agent, introduction of long chain branching, blending with high melt strength polymers and crosslinking have been proposed. In this review, these issues are discussed and analyzed in terms of mechanical, thermal, and rheological characterizations.